Politics of Oil and Gas in Ghana. Issue 2 (July 2016) - Graham, Emmanuel; Ackah, Ishmael; Gyampo, Ransford EdwardVan
The discovery of oil should transform economies, since oil revenues can be invested in infrastructure and the non-oil sector. Whilst oil discovery has transformed the economy of countries such as Indonesia, Norway and UK, the story is different in Sub-Saharan Africa. Available evidence in countries like Angola, Equatorial Guinea, and Nigeria suggests that economic growth has an inverse relationship with oil production. Some researchers have attributed this to lack of quality institutions and the politics surrounding oil production. In this study, we take a critical look at the politics of oil production in Ghana and its potential implications for the oil sector and national development.